PENGARUH EARNIG PER SHARE (EPS) DAN BOOK VALUE PER SHARE (BVS) TERHADAP NILAI PERUSAHAAN DENGAN HARGA SAHAM SEBAGAI VARIABEL INTERRVENING PADA SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2021 - Fitri, Nur; Wiryaningtyas, Dwi Perwitasari; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
The purpose of this study is to find out the effect of Earning Per Share (EPS) and Book Value Per Share (BVS) on firm value with share prices as an intervening variable in banking sector as many as 42 banking sectors listed on Indonesia Stock Exchange for 2019-2021 period. The sampling technique of this study uses purposive sampling by taking 14 samples as data analysis. Data analysis and hypothesis testing use smart PLS 3.0 application. The results of this study indicate that Earning Per Share (EPS) has a negative but not significant effect on stock prices, Book Value Per Share (BVS) has a significant negative effect on stock prices, while Earning Per Share (EPS) has a positive but not significant effect on firm value. Book Value Per Share (BVS) has a significant positive effect on firm value, stock prices have a significant positive effect on firm value, Earning Per Share (EPS) has a negative but not significant effect on firm value through stock prices, Book Value Per Share (BVS) has a significant negative effect on firm value through stock prices.